ANALISIS KINERJA LABA BERSIH PADA SUBSEKTOR TRANSPORTASI DI INDONESIA TAHUN 2021 - 2023 - Dera Pratiwi, Natasya; Satria, Indra; Chasbiandani, Tryas (Jurnal Ilmiah Akuntansi Pancasila (JIAP), 2025)
This study aims to analyze the net profit performance of transportation sub-sector companies during the period 2021 – 2023. The focus is to analyze the development trend of net profit performance, the main factors that influence it, and the different in performance over a certain period of time. This research method is quantitative descriptive. The population of this study is transportation sub-sector companies listed on the Indonesian Stock Exchange (IDX) from 2021 to 2023. The sample was determined using the purposive sampling method with the aim of obtaining samples that meet the research criteria. The total number of companies that were the research samples was 13 transportation sub-sector companies, with a research period of there years with a total sample of 39. The analysis in this study showed that net profit performance in 2021 to 2022 increased, which was mainly due to a decrease in the cost of good sold. However, net profit performance in 2022 to 2023 decreased, which was mainly due to an increase in expenses.